The Interplay of Poverty, Hardship, And Exploitation in Postcolonial Nigeria in Kaine Agary’s Yellow Yellow (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study analyzes Kaine Agary’s Yellow Yellow through the lens of postcolonial theory, examining the socio-economic, environmental, and gendered issues in postcolonial Nigeria, particularly in the Niger Delta. The novel reflects the region’s ongoing struggles with neocolonial exploitation, environmental degradation, and identity conflict, intensified by global capitalism and patriarchal structures. A gap exists in analyzing how these dynamics intertwine with postcolonial legacies in Nigerian literature. Using textual analysis, the study explores how Agary critiques these neocolonial forces, illustrating their devastating impact on both people and the environment. Key findings include the portrayal of economic exploitation, environmental degradation, and the marginalization of women, with Zilayefa, the protagonist, embodying the hybrid identity struggling for self-definition. The study recommends further exploration of gendered oppression within postcolonial frameworks and the development of policies to address resource control, environmental justice, and gender equality in postcolonial Nigeria.